2018
DOI: 10.1364/oe.26.017397
|View full text |Cite
|
Sign up to set email alerts
|

Electrically controllable THz asymmetric split-loop resonator with an outer square loop based on VO2

Abstract: In this paper, we propose an asymmetric split-loop resonator with an outer square loop (ASLR-OSL) based on vanadium dioxide (VO) which can actively control the transmission characteristics of a terahertz wave while maintaining a high quality factor of the asymmetric split-loop resonator (ASLR) by adding an outer square loop. The proposed ASLR-OSL demonstrated transmission characteristics similar to those of ASLR, and the transmission characteristics of ASLR-OSL were successfully controlled by directly applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…[63,[74][75][76][77][78][79][80] For example, a 1 mm by 1 mm sized array of gold slot nanoantennas resonating at ≈0.5 THz can be switched by a 500 V DC bias, with a 98% transmission tuning range (Figure 3a,b). Although electrical bias application is not considered a pure electrical process, it can still show a sufficiently fast switching speed (≈ns).…”
Section: Electrical Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…[63,[74][75][76][77][78][79][80] For example, a 1 mm by 1 mm sized array of gold slot nanoantennas resonating at ≈0.5 THz can be switched by a 500 V DC bias, with a 98% transmission tuning range (Figure 3a,b). Although electrical bias application is not considered a pure electrical process, it can still show a sufficiently fast switching speed (≈ns).…”
Section: Electrical Biasmentioning
confidence: 99%
“…[80] SRRs surrounded by a square fishnet grid over a 6 mm by 6 mm area on VO 2 can be electrically switched (Figure 4l,m). [80] SRRs surrounded by a square fishnet grid over a 6 mm by 6 mm area on VO 2 can be electrically switched (Figure 4l,m).…”
Section: Electrical Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining reconfigurable metasurfaces with VO 2 is a widely used approach for THz active metasurfaces, which usually trigger the insulator-to-metal phase transition mechanisms by thermal heating [84,140], optical excitation [138,141,142] and electrical field application [83,143]. Zhang et al [84] experimentally demonstrated that a meta-holography approach using a VO 2integrated metasurface can be used to dynamically tune the overall holographic image.…”
Section: (C) Two-dimensional Materials and Phase Transition Materials Fmentioning
confidence: 99%
“…Recently, Park et al fabricated a narrow-band filter in the terahertz frequency band by ingeniously designing the upper metal structure of a VO 2reconfigurable metamaterial and using the strong coupling characteristics of metal structure so that a driving voltage of only 5.5 V was required. However, the fabricated device showed a high insertion loss, and the maximum transmission rate was only 43% [19].…”
Section: Introductionmentioning
confidence: 98%